2014
DOI: 10.1016/j.tiv.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Use of in vitro human keratinocyte models to study the effect of cooling on chemotherapy drug-induced cytotoxicity

Abstract: A highly distressing side-effect of cancer chemotherapy is chemotherapy-induced alopecia (CIA). Scalp cooling remains the only treatment for CIA, yet there is no experimental evidence to support the cytoprotective capacity of cooling. We have established a series of in vitro models for the culture of human keratinocytes under conditions where they adopt a basal, highly-proliferative phenotype thus resembling the rapidly-dividing sub-population of native hair-matrix keratinocytes. Using a panel of chemotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
5
14
0
Order By: Relevance
“…Data showed that at low concentration of OMVs, the cells continued to grow rapidly leading to the increase of overall biomass compared with the control, and this was evident with the first concentration for the laboratory strain. These findings are consistent with that of (Al-Tameemi et al, 2014) who reported that stimulation of cells with low concentration of doxorubicin and 4-OH-CP led to an overall increase in HaCaT cells biomass. The results of the current study show that the most affected cells were the one exposed to the second concentration of hospital strain and the less affected cells were the first concentration of OMVs for laboratory strain.…”
Section: Discussionsupporting
confidence: 92%
“…Data showed that at low concentration of OMVs, the cells continued to grow rapidly leading to the increase of overall biomass compared with the control, and this was evident with the first concentration for the laboratory strain. These findings are consistent with that of (Al-Tameemi et al, 2014) who reported that stimulation of cells with low concentration of doxorubicin and 4-OH-CP led to an overall increase in HaCaT cells biomass. The results of the current study show that the most affected cells were the one exposed to the second concentration of hospital strain and the less affected cells were the first concentration of OMVs for laboratory strain.…”
Section: Discussionsupporting
confidence: 92%
“…We employed these models to study the effects of cooling on chemotherapy drug-mediated cytotoxicity. Using a panel of drugs (including both taxanes and anthracyclines) routinely used in the clinic for treatment of cancers such as breast cancer, we demonstrated for the first time that although the drugs were highly cytotoxic, cooling during drug treatment markedly reduced or even completely prevented drug cytotoxicity, in agreement with observations of the ability of scalp cooling to prevent HF toxicity in the clinic [13]. Equally importantly, we provided evidence that the precise cooling conditions (temperature) was a critical factor in determining the overall ability of cooling in rescuing cells from drugmediated toxicity.…”
Section: Introductionsupporting
confidence: 82%
“…Equally importantly, it was shown that the cooling conditions (temperature) used were also a critical factor in preventing cytotoxicity. These experiments provided for the first time biological evidence that progressive reduction of temperature (26°C, 22°C, 18°C, and 14°C) positively correlated with better protection (rescue) of keratinocytes from drug‐induced cell death . It is possible that cooling may have direct cytoprotective effects and at the same time may reduce drug diffusion that renders cells less susceptible to drug toxicity.…”
Section: Prevention Modalities Against Ciamentioning
confidence: 93%